Nanopartículas poliméricas de policaprolactona contendo resveratrol: efeito do TPGS nas propriedades físico-químicas e biológicas em câncer de mama in vitro e in vivo - Freitas, Paulo George Cavalcante de (2023)
Among the most studied molecules with antitumor potential currently, resveratrol stands out as a promising one, a phytoalexin that presents an inhibitory action of expectations and growths of several cancer cell lines. In this work, the application of this molecule against breast cancer is studied. In order to overcome the unfavorable characteristics presented by this drug, such as its solubility, it was decided to encapsulate resveratrol in polymeric nanoparticles based on poly-Ɛ-caprolactone, since nanoparticles act as an excellent drug carrier system, improving bioavailability, circulation time, and potentially reducing dose and side effects. The action of the pegylated surfactant TPGS (DL-α-tocopherol polyethylene glycol-1000) was also studied, a vitamin E derivative, which, in addition to acting on the stabilization and long circulation time of the nanoparticle, could reduce resistance to treatment with the drug. The nanoparticles were produced by the nanoprecipitation technique, with an average size of 145 nm or 129.5 nm and an average encapsulation efficiency of 97.31% or 93.21% for functionalized and non- functionalized formulations, respectively. Scanning electron microscopy indicated the production of spherical nanoparticles with low aggregation tendency. The DSC and FTIR techniques allowed the identification of the constituents, in addition to indicating the encapsulation of the drug in the amorphous or molecular state. Flow cytometry and confocal microscopy analyzes indicated an excellent concentration-dependent cell uptake of the produced nanoparticles, and showed that TPGS impairs the cell uptake process. In the cytotoxicity tests against breast cancer cells of the 4T1 lineage, IC 50 values were found corresponding to 0.12; 0.73; 4.06 μM for the formulation without TPGS, with TPGS and pure drug, respectively, showing the potentiation of the cytotoxic effect of resveratrol on polymeric nanoparticles, also impaired by the addition of TPGS. In vivo studies in an animal model corroborate previous data, demonstrating a better effect of the formulation without TPGS on tumor growth, in addition to drastically decreasing the daily growth rate of tumors compared to the groups with free drug and with functionalized nanoparticles, it was even less toxic than the formulation with TPGS that showed high levels of direct bilirubin, which marks damage to hepatocytes. Therefore, these results corroborate several scientific studies, being of great importance for understanding the effect of resveratrol encapsulation and the presence of TPGS effect against breast cancer, in vitro and in vivo.